Tidal Volumes and Outcome of Extubation in Mechanically Ventilated Premature Infants - Dassios, Theodore; Williams, Emma; Ambulkar, Hemant; Shetty, Sandeep; Hickey, Ann; Greenough, Anne (American Journal of Perinatology, 2020)
Objectives To compare the adjusted and unadjusted-for-weight tidal volume (VT) in ventilated prematurely born infants who were successfully extubated compared with the ones who failed extubation and explore the ability of VT to predict successful extubation.Study Design This is a two-center, prospective, observational, cohort study of ventilated infants born <32 weeks of gestational age (GA) at King's College Hospital and St George's University Hospital, London, United Kingdom between February and September 2018. Expiratory VT was recorded before extubation, and extubation was considered successful if the infants were not reintubated within 72 hours.Results Fifty-six (29 male) infants with a median (interquartile range) GA of 26 (25–29) weeks were studied. The infants who successfully extubated (N = 36) had a higher GA (27 [25–30] weeks) and VT (7.2 [4.8–9.5] mL) compared with the GA (25 [24–26] weeks) and VT (4.3 [4.0–5.5] mL) of the infants who failed extubation (p = 0.002 and p = 0.001, respectively). VT/kg was not different in infants who successfully extubated compared with the ones who failed extubation (p = 0.643). Following multivariate regression, VT was associated with extubation success (adjusted p = 0.022) and GA was not (adjusted p = 0.167). A VT > 4.5 mL predicted successful extubation with 82% sensitivity and 58% specificity (area under the curve = 0.786).Conclusion Successful extubation was associated with higher unadjusted-for-weight VTs compared with failed extubation, and unadjusted VT predicted extubation outcome with moderate sensitivity and specificity.
Keywords: extubation; tidal volume; prematurely born infants